2022
DOI: 10.36311/jhgd.v32.13365
|View full text |Cite
|
Sign up to set email alerts
|

Complexity theory in the management of patients with pain

Abstract: Nonlinear systems are not susceptible to being investigated with reductionist methods. In this sense, complexity theory offers an alternative approach to quantify the importance of contextual factors (CFs) in the patient with pain. The result of the positive (placebo) or negative (nocebo) use of CFs in the therapeutic setting could be responsible for a large part of a non-specific component of the efficacy of the treatment, directly affecting the quality of the results related to the patient's health (for exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Studies investigating patient education on pain reported reduction of pain and medication use, improvement of functional capacity [ 47 , 74 ], decrease in daily pain catastrophizing, morning disability, fatigue and anxiety, improvement of pain-related perceived control [ 64 ] and not seeking additional care [ 41 ], beyond those results reported under self-management courses/programs, which also included educational strategies. To cope with complexity in pain patient care, we must abandon linear models, accept unpredictability, respect (and use) autonomy and creativity, and respond flexibly to emerging patterns and opportunities [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating patient education on pain reported reduction of pain and medication use, improvement of functional capacity [ 47 , 74 ], decrease in daily pain catastrophizing, morning disability, fatigue and anxiety, improvement of pain-related perceived control [ 64 ] and not seeking additional care [ 41 ], beyond those results reported under self-management courses/programs, which also included educational strategies. To cope with complexity in pain patient care, we must abandon linear models, accept unpredictability, respect (and use) autonomy and creativity, and respond flexibly to emerging patterns and opportunities [ 88 ].…”
Section: Discussionmentioning
confidence: 99%